The Influence of Adaptive Leadership, Work Incentives and Job Rotation on Employee Performance with Work Morale as an Intervening Variable in the State Treasury Services Office Scope of Regional Offices of the Directorate General of Treasury, Central Java Province - Huda, Thoriqul (Asian Journal of Management Analytics, 2024)
This research aims to analyze the influence of adaptive leadership, work incentives and work rotation on employee performance through work morale. This research data uses primary data in the form of a questionnaire. The sampling method based on the Hair Sampling formula obtained a sample size of 135 respondents by determining respondents using Purposive Sampling with the criteria that the respondent was a permanent employee and had a minimum work period of 2 years. The data analysis used in this research is the Structural Equation Model. The results of this research state that adaptive leadership and work incentives have a positive and significant effect on work morale, work rotation does not have a positive and significant effect on work morale, adaptive leadership, work incentives, work rotation and work morale have a positive and significant effect on employee performance.